A Review on Healthcare System in Saudi Arabia: Opportunities and Obstacles - Abdulhameed G. Albeshr; Alanoud M. Alanazi; May M Aleraij; Setah T. Alanazi; Yazeed A. Alhabdan (Disease and Health: Research Developments Vol. 9, 2025)
Access to healthcare remains a significant challenge for many individuals, particularly in third-world countries. The ability to obtain healthcare services encompasses prevention, diagnosis, treatment, and the management of diseases, illnesses, disorders, and other health-impacting conditions. Like many nations, Saudi Arabia strives to deliver high-quality and cost-effective healthcare services to its population. In recent years, the overall health of the Saudi population has witnessed significant improvement. However, the healthcare system continues to face a range of complex mid- to long-term challenges. These challenges include the multifaceted roles of the Ministry of Health, limited financial resources, and evolving patterns of disease, among others. Healthcare services in Saudi Arabia are organized into four levels: primary, secondary, tertiary, and quaternary care. Recognizing the importance of healthcare, the Saudi Arabian government has invested substantial resources to enhance the system, with the ultimate goal of providing free and accessible healthcare services for all Saudi citizens and expatriates working in the public sector. This review aims to provide an overview of the healthcare system in Saudi Arabia and examine the challenges it currently faces. In conclusion, the path forward involves not only financial investment but also fostering collaboration across governmental and non-governmental sectors to implement evidence-based policies. Leveraging expertise, advancing digital health solutions, and prioritizing public health education will be essential components in overcoming these obstacles. With careful planning and determination, Saudi Arabia is well-positioned to lead by example in healthcare innovation and provision, ensuring equitable access and improved health outcomes for all its residents.